Factors Impacting Customer Loyalty of Online Shopping: A Case Study of China’s E-commerce Platforms - Lin, Luzi (Scholar: Human Sciences, 2023)
Purpose: This study investigates the factors impacting satisfaction, commitment, and customer loyalty of online shopping. The research establishes a theoretical framework based on the service quality model (SERVQUAL), e-service quality model (E-S-QUAL), e-tail quality model (eTailQ), theory of reasoned action (TRA), and customer loyalty model. Research design, data, and methodology: A total of 516 responses were collected from online questionnaires using step-by-step sampling, including purposive sampling, stratified random sampling, and convenience sampling. The respondents were customers who had online shopping experience on China’s top three e-commerce platforms and who shop online at least 1 to 2 times per week. The Structural Equation Model (SEM) and Confirmatory Factor Analysis (CFA) were used to analyze the data to verify the model’s goodness of fit and hypotheses. Results: The results showed that reliability, responsiveness, and privacy significantly and positively impacted satisfaction; however, web design did not significantly impact satisfaction. Satisfaction and perceived value had a significant impact on both commitment and customer loyalty, but commitment did not have a significant impact on customer loyalty. Conclusion: To improve customer satisfaction, commitment, and loyalty, it is necessary to focus on reliability, responsiveness, and privacy in e-services. Additionally, improving perceived value is essential for commitment and customer loyalty.